Potensi Suseptibilitas Magnetik dalam Monitoring Polusi Sedimen Sungai: Suatu Kajian Literatur - Mipantria Gabriela Pangkey; Meyke Virgin; Sayenne Givenshe Pungus; Glladyvio Derek; Bill Ryan Lucas; Intan Eka Audrey Loding; Vistarani Arini Tiwow (Fakultas Matematika Ilmu Pengetahuan Alam dan Kebumian, Universitas Negeri Manado, 2025)
A literature review of the magnetic mineral properties of river sediments using magnetic susceptibility parameters was conducted to assess their potential for pollution monitoring. This study analyzed 28 articles published in journals/proceedings related to the topic of magnetic susceptibility of river sediments. Based on the results of the literature review, the magnetic susceptibility values ​​of river sediments show a high range. This means that with such (high) susceptibility values, river sediments are ferrimagnetic. Information obtained from magnetic susceptibility data of river sediments indicates a high Fe content. We also describe that there are frequency-dependent magnetic susceptibility (χFD) values ​​of more than 2 % in river sediments containing superparamagnetic grains (fine grains). River sediments with high susceptibility values and high Fe content can indicate that the river has been polluted.